To the rescue of theology – Philip Clayton’s idea of emergent mind - Maziarka, Tomasz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
New worldview that arose from a number of important findings of science, including the Darwinian theory of evolution as well as the Big Bang theory, calls for a redefinition of the human place in the world of nature. Human mind, with its characteristic self-consciousness, is facing a difficult problem of understanding of his own nature as well as clarifying its relationship with the realm of the physical world. According to Philip Clayton, the correct answer to the question of the relation of mind to body (mind-body problem) is given by the concept of emergentism. While taking his arguments from modern science and philosophy, Clayton claims that the mind – causally active mental properties – is a valuable result of the evolution that has occurred through the emergence, and its special feature, i.e. rationality, sheds new light on attempts of the ultimate understanding of reality.